(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
In fact, the social experience of each person, his human image, qualities, and even defects are the product of communication processes. A person separated from society, deprived of the opportunity to communicate, can retain the qualities of an individual, but he cannot be a person. Therefore, we analyze its functions in order to imagine the importance of communication in personal development.